Let them not return : Sayfo : the genocide against the Assyrian, Syriac, and Chaldean Christians in the Ottoman Empire - Gaunt, David, 1944-; Atto, Naures; Barthoma, Soner Onder (War and genocide, 2017)
The mass killing of Ottoman Armenians is today widely recognized, both within and outside scholarly circles, as an act of genocide. What is less well known, however, is that it took place within a broader context of Ottoman violence against minority groups during and after the First World War. Among those populations decimated were the Indigenous Christian Assyrians (also known as Syriacs or Chaldeans) who lived in the borderlands of present-day Turkey, Iran, and Iraq. This volume is the first scholarly edited collection focused on the Assyrian genocide, or "Sayfo" (literally, "sword" in Aramaic), presenting historical, psychological, anthropological, and political perspectives that shed much-needed light on a neglected historical atrocity.